2022
DOI: 10.3390/diagnostics12071565
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning and Clinical-Radiological Characteristics for the Classification of Prostate Cancer in PI-RADS 3 Lesions

Abstract: The Prostate Imaging Reporting and Data System (PI-RADS) classification is based on a scale of values from 1 to 5. The value is assigned according to the probability that a finding is a malignant tumor (prostate carcinoma) and is calculated by evaluating the signal behavior in morphological, diffusion, and post-contrastographic sequences. A PI-RADS score of 3 is recognized as the equivocal likelihood of clinically significant prostate cancer, making its diagnosis very challenging. While PI-RADS values of 4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…A combination of AI and radiomics has been increasingly utilized in the field of urology, including prostate cancer in recent years. In addition to our study, Gravina et al also demonstrated that combining clinical information and radiological parameters with machine learning can better detect the prostate malignancy probability of equivocal prostate lesions [ 34 ].…”
Section: Discussionsupporting
confidence: 61%
“…A combination of AI and radiomics has been increasingly utilized in the field of urology, including prostate cancer in recent years. In addition to our study, Gravina et al also demonstrated that combining clinical information and radiological parameters with machine learning can better detect the prostate malignancy probability of equivocal prostate lesions [ 34 ].…”
Section: Discussionsupporting
confidence: 61%
“…Specifically, research into prostate cancer has demonstrated promising performances of ML models in detecting prostate cancer on MRI scans. Their best performing models achieved area under the curve (AUC) rates between 0.78 and 0.87 [38][39][40][41], surpassing the diagnostic performance of radiologists in one paper (AUC 0.81 vs. 0.69, p = 0.02) [39] and enhancing the specificity of PI-RADS assessment by senior radiologists in another (from 52.5% to 72.6%) [40].…”
Section: Discussionmentioning
confidence: 99%
“…It can extract multiple features from pathological findings and potentially define new markers of disease [183][184][185]. Radiomics has the potential to further increase the value of imaging in PC management; nevertheless, its introduction into current clinical practice is full of questions, as emphasized by several radiomic studies [186][187][188][189]. Several approaches have been proposed and standardization is the major issue.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%